Multi-omics analysis reveals metabolic regulation of phosphatidylcholine, triglycerides, phosphatidylethanolamine, and cardiolipin metabolism in mouse liver with metabolic dysfunction-associated steatotic liver disease - Hong Liang; Kang Song (PLoS ONE, 2025)
The dysregulation of phosphatidylcholine (PC), triglycerides (TG), phosphatidylethanolamine (PE), and cardiolipin (CL) metabolism is believed to contribute to the development of MASLD. However, little is known about the mechanisms underlying the onset of this condition. To establish a mouse model of MASLD, C57BL/6J mice were fed a high-fat diet (HFD). Lipidomics was applied to identify differences in liver lipids. RNA-sequencing and bioinformatics analyses were conducted to investigate changes in the expression of genes and pathways associated with these metabolic processes. 49 lipid classes and 3221 lipid species were identified using positive- and negative-ion pattern identification. A total of 678 differentially expressed genes were identified, of which 364 were upregulated and 314 were downregulated in the MASLD group. KEGG enrichment pathway analysis highlighted the downregulation of four genes such as Gpat4 , Gpcpd1 , Chkb , and Etnppl. These findings contribute to our understanding of the metabolic changes associated with MASLD.